Utilization of rare codon-rich markers for screening amino acid overproducers - Bo Zheng (Nature Portfolio, 2018)
Current toxic analogues-based amino acid overproducer screening method cannot provide accuracy, sensitivity and high throughput simultaneously. Here, the authors use rare codon rich marker for the selection of overproducers of multiple amino acids from random mutation libraries of E. coli and C. glutamicum.